Corrosion Protection of Hot Dip Galvanized Steel in Mortar - Figueira,Rita M. (2013)
Corrosion of steel in concrete is one of the major causes of structure degradation, requiring expensive maintenance. The using of hot dip galvanized steel (HDGS) has been recognized as one effective measure to increase the service life of reinforced concrete structures in marine environmental. However, HDGS corrodes in contact with high alkaline environment of fresh concrete. Although this initial corrosion process allows the formation of a protecting layer barrier, the corrosion that occurs initially is harmful and chromate conversion layers are usually used to prevent it. Due to toxicity of Cr(VI), these kinds of pre-treatments have been forbidden and hybrid coatings have been proposed as alternatives [1-3]. To evaluate the performance of these coatings, beyond the laboratory characterization, in situ tests in real conditions should be performed. An electrochemical system to measure the macrocell current density (i gal) was designed to evaluate the degradation of HDGS coated samples with different organic-inorganic hybrid films, embedded in mortar during 70 days, using an automatic data acquisition system. This system revealed to be feasible and highly sensitive to coatings degradation. Also, allow distinguishing different hybrid coatings with different thicknesses.